Professionalism and Information Technology: Positioning and Mediation - Thomas Ley; Udo Seelmeyer (Social Work and Society)
The starting point of this paper is the assumption that - on the one hand - information technology (IT) is increasingly shaping the professional knowledge base and on the other the relation between organisation and profession. IT is changing the role, responsibilities and practices of social workers and therefore it is important to deal with the impact of IT on social work (representative for many: Harlow and Webb 2003; Burton and van den Broek 2008). Hence, the general aim of this paper is to stimulate a basic discussion on"IT application in social worke", or rather, in a more general way, on "technology and professionse". Secondly, it is about an analytical differentiation of the process of informatisation, respectively formalisation. Thirdly we want to discuss the assumption and overall combination of efficiency, effectiveness and IT. Therefore this paper is arranged as follows: After some opening remarks (chapter 1) we outline case management systems as research object (2). Further on, we confront the approach of reflexive professionalism (3) with the process of formalization (4). Subsequently, we touch on the debate of"technologies of care" (5) and conclude with some short remarks on a research program (6).